Edukasi Identifikasi Masa Kadaluarsa Obat dan Perhitungan Beyond Use Date pada Pasien Instalasi Farmasi Rawat Jalan di RSUD dr. R. Koesma Kabupaten Tuban - Iskandar Iskandar; Byba Meida; Devi Ristian Octavia (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Public knowledge about health, especially medicine is still very limited. One of the terms of health in medicine that is less known by the public is BUD (Beyond Use Date). BUD is time limit for the use  of  medicinal products after being prepared/formulated or after the primary packaging is  opened /tampered with. While ED (Expiration Date) is the time limit for the use of medicinal products after being  produced by the manufacturer before the packaging is opened. ED is listed by the manufacturer on the packaging while BUD is not always listed. Providing correct information about BUD becomes the  needs of the community  to avoid negative impacts that may arise,such as: the occurrence of medication error, the target therapy is  not optimal and decreases the effectiveness of the medicinal products. For this reason, an effort  is needed to increase public knowledge about BUD, namely through counseling activities with lecture, discussion and Q&A methods. Counseling on BUD (Beyond Use Date) in patients of Hospital Outpatient Pharmacy Installationt dr.R.Koesma Tuban Regency, aims to find out  the level of public knowledge of BUD. Based on the evaluation results of the pre test question sheet (before counseling) and post test question sheet (after counseling) most of the participants increased their knowledge,its means that the participants understood the definition and the difference between BUD and ED solid, semi-solid, liquid, eye drops and insulin preparations.